BIOGRAFI DAN PEMIKIRAN H.M. RASYIDI - Miftakhur Ridlo (HUMANISTIKA : Jurnal Keislaman, 2023)
This article discusses the biography and thoughts of H.M. Rasyidi, a very productive thinker, but his name is foreign to the ears of academics. He has an extraordinary contribution to Indonesia and even other countries such as America and France. In this research, the writer uses the pure library research method. All works related to this research are used as reference material to read the thoughts of the characters. To support this research, the analytical methods that the author uses are descriptive, interpretative and historical continuity. H.M Rasjidi was the first Indonesian Minister of Religion. In government, he has also served as the Indonesian Ambassador to Egypt, Saudi Arabia and others. Previously in the field of organization, he was involved in the PII and Masyumi organizations, among others. He has also been active as a Lecturer at the Islamic College (UII) Yogyakarta, Professor of the UI Faculty of Law, Professor of Western Philosophy at IAIN Syarif Hidayatullah and a visiting Lecturer at McGill University. H.M. Rasjidi is of the opinion that Islamic law concerning matters of worship and its details clearly cannot be changed, because this will open up opportunities for the creation of new ways of worship like other religions. Philosophical truths are called speculative truths because they talk about abstract things that cannot be tested or researched. While the truth of science is called positive truth because it can be tested empirically. He said that the Christianization of Muslims is clearly prohibited because in government regulations it is not permissible to "promote" religion to be embraced by people who have embraced (Islam).